Glucose increases endothelial-dependent superoxide formation in coronary arteries by NAD(P)H oxidase activation: attenuation by the 3-hydroxy-3-methylglutaryl coenzyme a reductase inhibitor atorvastatin - Christ, Michael; Bauersachs, Johann; Liebetrau, Claudia; Heck, Marina; Günther, Andreas; Wehling, Martin (Diabetes, 2002)
Increased vascular superoxide anion (O2−) formation is essentially involved in the pathophysiology of atherosclerosis. Chronic hyperglycemia induces endothelial dysfunction, probably due to increased formation of reactive oxygen intermediates. However, little is known about the localization, modulators, and molecular mechanisms of vascular O2− formation during hyperglycemia. In porcine coronary segments, high glucose significantly increased O2− formation (1,703.5 ± 394.9 vs. 834.1 ± 91.7 units/mg for control, n = 64, P < 0.05; measured by lucigenin-enhanced chemiluminescence). This effect was completely blocked after removal of the endothelium. Coincubation with 10 μmol/l atorvastatin, a lipophilic inhibitor of 3-hydroxy-3-methylglutaryl-coenzyme A reductase, attenuated basal and glucose-induced O2− formation (328.1 ± 46.5 and 332.8 ± 50.3 units/mg, P < 0.05 vs. without atorvastatin). Incubation with mevalonic acid reversed this effect. High glucose increased mRNA expression of the oxidase subunit p22phox, which was blocked by 10 μmol/l atorvastatin, whereas expression of gp91phox was unchanged. In conclusion, glucose-induced increase of vascular O2− formation is endothelium dependent and is probably mediated by increased p22phox subunit expression. Beneficial effects of statins in diabetic patients may be explained in part by attenuation of vascular O2− formation independent of lipid lowering.